2019
DOI: 10.1155/2019/5426080
|View full text |Cite
|
Sign up to set email alerts
|

How Have Travelers Changed Mode Choices for First/Last Mile Trips after the Introduction of Bicycle-Sharing Systems: An Empirical Study in Beijing, China

Abstract: In recent years, there has been rapid development in bicycle-sharing systems (BSS) in China. Moreover, such schemes are considered promising solutions to the first/last mile problem. This study investigates the mode choice behaviors of travelers for first/last mile trips before and after the introduction of bicycle-sharing systems. Travel choice models for first/last mile trips are determined using a multinomial logit model. It also analyzes the differences in choice behavior between the young and other age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 36 publications
1
38
0
4
Order By: Relevance
“…However, it has reduced the usage of private cars and taxis [5], especially their usage in short trips in downtown areas [1,32,33]. Both Fan et al [34] and Shaheen et al [5] pointed out that the reductions in car use were partly because of the integration of bike sharing and public transit in the first and last mile of the trips. Interestingly, Yang et al [35] concluded that the percentage of car ownership of metro bike-sharing users (48.8%) was twice as high as the percentage of car owners in the study area (19.7%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it has reduced the usage of private cars and taxis [5], especially their usage in short trips in downtown areas [1,32,33]. Both Fan et al [34] and Shaheen et al [5] pointed out that the reductions in car use were partly because of the integration of bike sharing and public transit in the first and last mile of the trips. Interestingly, Yang et al [35] concluded that the percentage of car ownership of metro bike-sharing users (48.8%) was twice as high as the percentage of car owners in the study area (19.7%).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considerable attention is paid by scientific studies to modeling the behavior of individuals when traveling. In particular, determining the utility function to assess the attractiveness of bicycle use after the introduction of a system of the shared use of bicycles to travel the "first/last mile" in Beijing (China) was reported in work [11]. The authors described the function of calculating the probability of choosing such modes of movement as walking on foot, riding own bike, a bike from the BSS system (Bicycle-Sharing Systems), and driving own car.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Recommended actions for increasing subway ridership in NYC include adding Citi Bike stations with a careful consideration of a 0.25 mile radius from the subway station, which is in accordance with other studies (Ma et. al, 2015;Fan et. al, 2019;Campbell and Brakewood, 2017) and this study findings.…”
Section: Chapter 7: Recommendations and Future Research Directionsmentioning
confidence: 98%
“…A 10% increase in annual CaBi ridership contributed to a 2.8% increase in average daily Metrorail ridership. Fan et al (2019) investigated the mode choice behaviors of travelers for first/last mile trips before and after introducing bicycle-sharing systems in Beijing, China. They applied the multinomial logit model to determine travel choice models for first/last mile trips, determining that shared bicycles quickly become the preferred mode over walking.…”
Section: Chapter 2: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation